Genotypic differentiation of Monilinia spp. populations in Serbia using a high-resolution melting (HRM) analysis - Antonios Zambounis; Eleni Stefanidou; Panagiotis Madesis; Jovana Hrustić; Milica Mihajlović; Brankica Tanović (Plant Protection Science, 2021)
Monilinia laxa, Monilinia fructicola and Monilinia fructigena are the three main causal agents of brown rot, which is one of the most important diseases of stone fruits in pre- and postharvest conditions. Nowadays, the need for the precise genotyping of these Monilinia species in terms of the genetic diversity of their populations or differences in their pathogenicity and host range is a prerequisite for any efficient disease management. In our study, the genetic structure of Monilinia populations in Serbia from three geographically distinct regions was investigated employing a high-resolution melting (HRM) analysis which is a sensitive and rapid molecular approach in fungal genotyping and diagnostics. Using species-specific primer pairs genotype-specific HRM melting curve profiles were generated allowing to efficiently decipher the genetic diversity of the Monilinia populations. The Monilinia genotypes could be easily distinguished according to their melting curves. The isolates from the northern region were assigned to distinct genotypes and grouped rather independently compared to the isolates of the other two regions among all three tested Monilinia spp. M. fructicola and M. fructigena showed a higher genetic diversity among their populations (44%) compared with the genetic diversity among the M. laxa populations (7%). In contrast, the genetic variance within the pathogen populations was higher in the case of M. laxa (93%). Our data revealed an absence of host specificity in the Monilinia spp. populations.